ISLÂM DAN PEREKONOMIAN ISLÂM DALAM PEMERINTAHAN MODERN - Nashar - (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
the basic 0f Islamic ekonomy, it is actuallydifferent with the basic of Modern Economic System.Because of the view of islam for ekonomy have thecharacteristic what may be in Modern Economic System.Islam has the guidence based the Al-Qur’ an and Hadistand the guidence has the interpretation. The systemdifference between Islam versus Modern System bears aconclusion : Islamic Ekonomy continuesly and by the allaspects compleyely concerning humanism. Islam has aeconomic system having the principle of responsibilitytowards a social community, social living have ability andpopulation economic stimulation. So for the last wise isdone by government will always relate with all element ofsociety. There are some economic system is not ruled yet inthe sources of Islamic law, as the poroblems of ekonomicsystem; BUDGET, so it needs to be new Ijtihad, therefore,that system always bases on the social service and in linewith the guidence of islamic law.